Penerapan Metode Pemberian Tugas Melalui Media Powerpoint untuk Meningkatkan Motivasi dan Hasil Belajar PKn Siswa Kelas XI-MIA 1 pada Pembelajaran Daring di SMA - Sugianto, Sugianto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
This research was carried out with the aim of increasing the motivation and learning outcomes of Civics in online learning for students of class XI-MIA 1 at SMA Negeri Sekotong, West Lombok Regency, odd semester of the 2020/2021 academic year through PowerPoint media. This type of research is Classroom Action Research (CAR). The subjects were students of class XI-MIA 1 at SMA Negeri Sekotong, West Lombok Regency, in the odd semester, with a total of 22 students. Classroom Action Research Design (CAR) uses the Kemmis & Mc.Taggart model which includes planning, action, observation, and reflection. Data collection techniques using observation and tests. The data analysis technique used is descriptive quantitative and qualitative. The results showed that there was an increase in Civics learning outcomes, this can be seen from the KKM completeness of pre-action students and each cycle the average result of the observations in cycle I was 75.18 in the sufficient category, while cycle II was 76.61 in the good category and experienced an increase . According to the success indicators set, the classical completeness criteria at XI-MIA 1 Sekotong State Senior High School, West Lombok Regency is ≥76. In the initial data, classical learning completeness was an average of 75, then the average in the first cycle was 75.18 and in the second cycle it became 76.71. While individual completeness in the initial data of students who were able to fulfill KKM ≥ 75 were only 16 people (57.14%), while in cycle I there were 28 students (64.29%), then in cycle II it became 28 students (85, 71%). Thus, it can be concluded that online learning using PowerPoint media can increase the motivation and learning outcomes of students' Civics.